Variable major lipoprotein is a principal TNF-inducing factor of louse-borne relapsing fever. - Vidal, V; Scragg, I; Cutler, S; Rockett, K; Fekade, D; Warrell, D; Wright, D; Kwiatkowski, D (1998)
Massive release of tumor necrosis factor is responsible for the potentially fatal larisch-Herxheimer reaction that follows antibiotic treatment of relapsing fever due to Borrelia recurrentis. We have undertaken the quantitative purification of the components of B. recurrentis that stimulate human monocytes to produce tumor necrosis factor. We show that the predominant factor inducing tumor necrosis factor is a variable lipoprotein homologous to the variable major protein of B. hermsii. We found antibodies to different forms of variable major protein in two patients with louse-borne relapsing fever. The three purified variable major proteins studied here differ in their ability to induce tumor necrosis factor production, which may partly explain the variable clinical severity of borrelial infection. These results may be of considerable relevance for the pathogenesis of Lyme disease and other forms of human borreliosis.